A New Test for Irony Detection: The Influence of Schizotypal, Borderline, and Autistic Personality Traits - Kieckhäfer, Carolin; Felsenheimer, Anne K.; Rapp, Alexander Michael (Frontiers in Psychiatry, 2019)
Irony has repeatedly been suggested as a language based social cognition task. It has been argued to show specific variances in psychiatric disorders and healthy adults with certain personality traits. Above that, irony comprehension is based on a complex interplay of the informational context, the relationship of the conversational partners, and the personality of the recipient. The present study developed a video-based German language test for a systematic examination of irony detection accuracy (Tuerony). The test includes (i) a stereotypical conversation partner (doctor, actor) in (ii) different perspectives (direct interaction, neutral observer) and (ii) a bilateral chat history on a conventional messenger service interface with ironic criticism, ironic praise, literal criticism and literal praise. Based on the continuous approach of psychiatric symptoms, schizotypal, borderline and autistic personality traits were associated with irony detection accuracy in a healthy sample. Given the often reported role of mentalization in irony detection, these associations were also investigated. First, a broad variance of irony comprehension in our healthy sample could be shown. Second, schizotypal and borderline, but not autistic traits were significantly negatively associated with irony detection accuracy. Finally, in the current healthy sample, neither variation of the conversational context nor mentalization characteristics were significantly associated with performance beyond personality traits. The current results therefore highlight two aspects for future research in irony comprehension: the importance of ecological valid tests and the role of the individual personality of the recipient.